Rasch model statistics for PPB. - Magdalena Chęć (21029951) (2025)
Background Adverse childhood experiences, such as abuse, maltreatment or neglect, can lead to many mental disorders and emotional and social difficulties. Objective The aim of this study was to adapt and validate the ‘Maltreatment and Abuse Chronology of Exposure’ (MACE) questionnaire to Polish socio-cultural conditions. Participants and setting The study involved 330 adult, white people (60.8% women); aged between 18 and 86 years (M =  41.01; SD =  14.67), with and without a psychiatric diagnosis. Methods Convergent validity was assessed by comparing MACE (PL) scores with the CTQ (Childhood Trauma Questionnaire) and ACE (Adverse Childhood Experience Questionnaire), while predictive validity was determined by examining the relationships between MACE (PL) scores and the SCL-90 (Symptom Checklist-90). The psychometric properties of the scale were assessed using Rasch analysis, which evaluated item fit, difficulty, and person separation. Internal consistency was measured using the Kuder Richardson coefficient (KR-20). The Polish version of MACE demonstrated good reliability, as indicated by high internal consistency (KR-20) and findings from Rasch analysis. Results The Polish version of MACE, after analysis, included a total of 58 items combined into 10 scales. The Polish version of the scale showed high internal consistency, measured using the Kuder-Richardson formula (KR-20). The results of the Polish version of MACE showed strong and positive correlations with the scores of CTQ and ACE. These correlations were particularly evident for the overall MACE scores and subscales such as MACE SUM, MACE Multiplicity, and MACE Duration. Correlations for physical neglect and emotional neglect were moderate but statistically significant (r =  0.49, p <  0.001; r =  0.46, p <  0.001). MACE scores were positively correlated with SCL-90 and ACE results, indicating high predictive validity in relation to psychopathological symptoms. The correlations between MACE and SCL-90 were moderate but significant, suggesting that MACE effectively predicts psychopathological symptoms associated with childhood trauma. Most MACE subscales showed moderate reliability (0.5–0.8), except for the PVA and SEXA subscales, which demonstrated high internal consistency (KR20 >  0.8). Conclusion The Polish version of MACE demonstrates solid convergent validity, predictive validity, and psychometric reliability, making it a valuable tool for assessing experiences of maltreatment and neglect during childhood in both research and clinical practice. Assessing the history of adverse childhood experiences using the MACE can provide a more precise understanding of how the type and timing of these experiences influence outcomes. This, in turn, sheds light on the mechanisms underlying health and the common pathways contributing to overlapping symptom spectrums. In summary, the MACE appears to be a valuable tool for clinicians and researchers aiming to retrospectively assess the types, timing, and duration of childhood maltreatment experiences during sensitive developmental periods in adulthood.